2019
DOI: 10.3389/fphys.2019.01229
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis-Associated Enteric Glial Cell Immune-Activation and Redox Imbalance Modulate Tight Junction Protein Expression in Gulf War Illness Pathology

Abstract: About 14% of veterans who suffer from Gulf war illness (GWI) complain of some form of gastrointestinal disorder but with no significant markers of clinical pathology. Our previous studies have shown that exposure to GW chemicals resulted in altered microbiome which was associated with damage associated molecular pattern (DAMP) release followed by neuro and gastrointestinal inflammation with loss of gut barrier integrity. Enteric glial cells (EGC) are emerging as important regulators of the gastrointestinal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 50 publications
1
34
1
Order By: Relevance
“…A more recent meta-analysis suggests that at least IBS is characterized at the genus level by decreases in Lactobacillus and Bifidobacterium and increased levels of Escherichia coli and Enterobacter (both in the Proteobacteria phylum) without changes in Bacteroidetes and Enterococcus 6 . Both of these outcomes are not fully recapitulated in Veterans with GWI 13 or in rodent models of this disorder [14][15][16] , including the results of the present study. Third, GWI is not IBS and likely encompasses a different set of pathological alterations such that some Veterans with GWI have GI disturbances while others do not 1,13 .…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A more recent meta-analysis suggests that at least IBS is characterized at the genus level by decreases in Lactobacillus and Bifidobacterium and increased levels of Escherichia coli and Enterobacter (both in the Proteobacteria phylum) without changes in Bacteroidetes and Enterococcus 6 . Both of these outcomes are not fully recapitulated in Veterans with GWI 13 or in rodent models of this disorder [14][15][16] , including the results of the present study. Third, GWI is not IBS and likely encompasses a different set of pathological alterations such that some Veterans with GWI have GI disturbances while others do not 1,13 .…”
Section: Discussioncontrasting
confidence: 72%
“…Therefore, the three main symptom clusters of GWI can be linked individually to gut dysbiosis, suggesting the possibility that a disrupted microbiome underlies all three. Indeed, a very small number of recent studies has confirmed that the gut microbiome is altered in Gulf War Veterans 13 and in animal models of GWI [14][15][16] .…”
mentioning
confidence: 99%
“…However, the present study is limited in its more in-depth mechanistic approach about the structure of SsnB since it does not probe or characterize of the chemical moiety of acetylated SsnB. Notably, gastrointestinal inflammation is also triggered by activation of the enteric glial cells as shown by us previously [7]. Though we did not explore the role of SsnB in modulating the glial cells that are an integral part of the enteric nervous system, it is worth studying the TLR4 antagonism in these pathways [10,36].…”
Section: Discussionmentioning
confidence: 86%
“…Our group was the first to report that the GWI mouse model exhibited significant alteration of the gut microbiome, leading to gut leaching, increased endotoxemia, and Toll-like receptor 4 (TLR4) activation which established a mechanistic connection between gastrointestinal and neuroinflammation [6]. We have further confirmed that the administration of the Gulf War (GW) chemicals in mice led to the activation of enteric glial cells through the Toll-like receptor (TLR) pathway [7]. Though there has been extensive research on the underlying pathobiology of GWI over the past decade, yet there are few reported therapeutic approaches specific for GWI that target the Toll-like receptors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation